Analisis Efisiensi Pemasaran Usaha Budidaya Jamur Tiram Putih di Kota Mataram - FR, Aeko Fria Utama; Nursan, Muhammad; Rakhman, Amry (Lembaga Intelektual Muda (LIM) Maluku, 2024)
One of the factors that can influence the success of the mushroom business can be seen from the marketing channels and marketing efficiency of the oyster mushroom cultivation business. This research aims to analyze channel profits and marketing efficiency of white oyster mushroom cultivation businesses in Mataram City. The method used in this research is a descriptive method, collecting data obtained using survey and interview techniques. The unit of analysis is the oyster mushroom cultivation business in Mataram City. The determination of the area in this study was determined by